2006
DOI: 10.1248/bpb.29.321
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clonidine Orally Disintegrating Tablet for Pre-anesthetic Medication in Pediatric Surgery

Abstract: Clonidine hydrochloride (CL), an a 2 -adrenoceptor agonist, is currently used for pre-anesthetic medication owing to its sedative and analgesic properties.1-3) These unique properties provide pre-operative sedation and preventing post-operative pain and vomiting in pediatric patients, as well as adults. [4][5][6][7] One drawback for this medicine applying to pediatric patients is difficulty in taking. To overcome this problem, several formulations including lollipop have been developed so far. [8][9][10] We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…High bioavailability (75–100%) has been described after oral administration in adults (9,10). Although the type of oral formulation may influence observed concentrations (11), no pediatric data regarding oral bioavailability have been published. Despite the lack of pediatric data, the bioavailability described in adults has been extrapolated to the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…High bioavailability (75–100%) has been described after oral administration in adults (9,10). Although the type of oral formulation may influence observed concentrations (11), no pediatric data regarding oral bioavailability have been published. Despite the lack of pediatric data, the bioavailability described in adults has been extrapolated to the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the time taken to consume a lollipop could be variable between patients. A further study found that orally disintegrating tablet formulations were superior to lollipops in reaching satisfactory sedation . A summary of oral transmucosal formulations identified in the literature search are presented in Table .…”
Section: Oral Transmucosal Routementioning
confidence: 99%
“…Lollipop formulations identified in this literature search were sweetened with sucrose and starch syrup, but excipients used to improve the palatability of the ODTs and sublingual tablets were not described . No study provided data on taste acceptability from patients.…”
Section: Oral Transmucosal Routementioning
confidence: 99%
See 2 more Smart Citations